معيار الإعلامية لدى روبرت دي بوجراند وتجلياته في آيات القرآن الكريم: دراسة دلالية = The manifestation of Robert De Beaugrande’s standard of informativity in the Quranic verses: a semantic study - Mustapha, Nik Hanan; Abdullah, Mohd Ikhwan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia., 2018)
يتناول هذا البحث موضوع الإعلامية التي تعْنى بمدى ما يتصف به النص من عناصر متوقعة مقابل عناصر غير متوقعة ومعلومة مقابل غير معلومة بالنسبة للمتلقين، ويقصد بالمتلقين في هذا البحث متلقو القرآن الكريم على وجه الخصوص. وبما أنّ النصوص القرآنية نصوص إلهية، فمن المتوقع أن تتميّز إعلاميته من سائر النصوص البشرية؛ ولذا، يهدف هذا البحث إلى إبراز بعض تجليات الإعلامية العامة في القرآن الكريم من خلال المحاور التالية: الآيات المتشابهة، و"اللغة الجديدة"، والحروف المقطعة، والإشارات العلمية في القرآن. وقد تمّ مناقشة هذه المحاور المختصة بالقرآن في ضوء الإطار العام لمبادئ نظرية الإعلامية، وبيان أثر هذه التجليّات الإعلامية في التلقي عند الجاهليين، والعلماء القدامى والمعاصرين. وتوصّل الباحثان إلى أنّ القرآن يحتوي على درجات مختلفة من الإعلامية، بعضها منخفض وهو المحكم من الآيات، وبعضها مرتفع وهو المتشابه من الآيات، وأن القدامى من المفسرين والعلماء قد بذلوا جهودهم في خفض إعلامية القرآن الكريم من خلال القرآن نفسه، والحديث الشريف، وأقوال الصحابة والتابعين، ومن خلال الإشارات العلمية، وكذلك أن القرآن يحمل رسالة خالدة، يتماشى مع كل عصر من العصور، يصدّق كل ما توصل إليه العلماء في العصر الحديث، وأنّ إعلاميته تفوق إعلامية النصوص البشرية لأنه علم الله فوق كل شيء. ********************************************************* This paper studies the topic of informativity which concerns about to what extent a text is expected or unexpected, known or unknown for the receivers, namely –in this paper-the receivers of the Quran. As the Quran is the word of God, we believe that the Quranic texts have distinctive features of informativity as compared to human texts. Therefore, we carry out this study to highlight some of the general manifestations of informativity of the Quran based on the following themes: Allegorical verses, “new language”, Quranic initials, and scientific signs in the Quran. These Quranic themes were discussed in the light of general framework of informativity theory. Besides that, we also discussed the effects of informativity of the Quran on pre-Islamic society traditional as well as contemporary Muslim scholars. We conclude that the Quranic texts comprise of different grades of informativity, some of them are low and it is the same as the concept of ‘clear verses’ (muhkam) and some of them are high in informativity which are equivalent to the concept of ‘allegorical verses’(mutasyabih). Muslim scholars have put their utmost efforts to downgrade the informativity of the Quran using Quranic verses itself, hadith, companion sayings as well as the scientific signs. We also conclude that the Quran brings eternal message that consistent with all time and it asserts many of the scientific findings. Overall, we could say that the informativity of the Quran goes beyond the informativity of human texts because Allah’s knowledge is beyond time and space. *********************************************************** Kajian ini membincangkan tajuk nilai maklumat (informativity) yang berkenaan dengan sejauh mana sesuatu teks itu boleh dijangka atau tidak, boleh diketahui atau tidak bagi penerima (receiver) atau pembaca yang mana dalam kajian ini merujuk kepada penerima dan pembaca teks Al-Quran. Sebagai kalam Tuhan, kita beriman bahawa teks Al-Quran mengandungi ciri-ciri informatifiti yang istimewa berbanding teks ciptaan manusia. Atas dasar itu, kami menjalankan kajian ini bagi menjelaskan sebahagian manifestasi umum bagi ciri-ciri informatifiti Al-Quran berdasarkan tema-tema berikut: 1- Ayat-ayat mutasyabihat, ‘bahasa baharu’, huruf-huruf abjad pada permulaan surah, dan petanda-petanda saintifik dalam Al-Quran. Selain itu, kami juda membincangkan tentang kesan informatifiti Al-Quran terhadap masyarakat Arab jahiliyah dan para sarjana kontemporari. Kajian merumuskan bahawa Al-Quran mengandungi pelbagai peringkat informatifiti yang mana sebahagiannya rendah sekaligus bersamaan dengan konsep ayat-ayat muhkam manakala sebahagian ayat yang lain mengandungi informatifiti yang tinggi. Ini sejajar dengan konsep ayat-ayat mutasyabihat. Para sarjana Islam telah berusaha gigih untuk merendahkan tahap informatifiti Al-Quran menggunakan ayat-ayat Al-Quran sendiri, hadith, kata-kata para sahabat dan malahan petanda-petanda saintifik yang terkandung dalam Al-Quran. Umumnya, boleh kita katakan bahawa tahap informatifiti Al-Quran melangkaui batas nilai maklumat teks manusia kerana ilmu Allah tiada batasan masa dan ruang.